Sosialisasi perilaku hidup bersih dan sehat (PHBS) di lingkungan Sekolah Dasar Negeri 01 Bantar - Hendy Suhendy; lutfi Nur Iskandar; Dayu Putri; Lisma Dwi Putri; Liya Ameliya; Nanda Kamila Sabrina; Pia Yuniar (Universitas Mataram, 2023)
Clean and healthy living behavior (PHBS) is a set of behaviors performed on an awareness basis, helping families, groups or communities to help themselves (independently) in the field of health and contribute to their health. Active role in achieving the common goal, health. The majority of children walk out from their house so when they are at school they have to wash their hands, but they are used to not washing their hands while poor sanitation and hygiene can increase the risk of poisoning or infection. The purpose of this community service activity is to increase the knowledge of Bantar 01 Public Elementary School children regarding the importance of PHBS and proper hand washing. The community service activity method was by lecturing and giving questionnaires. The result of the activity is an influence on the understanding of the material received based on gender.